The Theory of Optimal Taxation: New Developments and Policy Relevance - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2009)
The theory of optimal taxation has often been criticized for being of little practical policy relevance, due to a lack of robust theoretical results. This paper argues that recent advances in optimal tax theory has made that theory easier to apply and may help to explain some current trends in international tax policy. Covering the taxation of labour income and capital income as well as indirect taxation, the paper also illustrates how some of the key results in optimal tax theory may be derived in a simple, heuristic manner.
Keywords: H21; H24; H25; 330; optimal taxation; uniform taxation; tax neutrality; Optimale Besteuerung; Einkommensteuer; Unternehmensbesteuerung; Indirekte Besteuerung; Steuertheorie